Reef communities associated with 'dead' cold-water coral framework drive resource retention and recycling in the deep sea. (September 2021) - Maier, Sandra R.; Mienis, Furu; de Froe, Evert; Soetaert, Karline; Lavaleye, Marc; Duineveld, Gerard; Beauchard, Olivier; van der Kaaden, Anna-Selma; Koch, Boris P.; van Oevelen, Dick
Abstract: Cold-water coral (CWC) reefs create hotspots of metabolic activity in the deep sea, in spite of the limited supply of fresh organic matter from the ocean surface (i.e. phytodetritus). We propose that 'dead' coral framework, which harbours diverse faunal and microbial communities, boosts the metabolic activity of the reefs, through enhanced resource retention and recycling. Analysis of a video transect across a 700-540 m-deep CWC mound (Rockall Bank, North-East Atlantic) revealed a high benthic cover of dead framework (64%). Box-cored fragments of dead framework were incubated on-board and showed oxygen consumption rates of 0.078–0.182 μmol O2 (mmol organic carbon, i.e. OC) −1 h −1, indicating a substantial contribution to the total metabolic activity of the CWC reef. During the incubations, it was shown that the framework degradation stage influences nitrogen (re)cycling, corresponding to differences in community composition. New (less-degraded) framework released ammonium (0.005 ± 0.001 μmol NH4 + (mmol OC) −1 h −1 ), probably due to the activity of ammonotelic macrofauna. In contrast, old (more-degraded) framework released nitrate (0.015 ± 0.008 μmol NO3 − (mmol OC) −1 h −1 ), indicating that nitrifying microorganisms recycled fauna-excreted ammonium to nitrate. Furthermore, the framework community removed natural dissolved organic matter (DOM) from the incubation water (0.005–0.122 μmol C (mmol OC) −1 h −1 ). Additional feeding experiments showed that all functional groups and macrofauna taxa of the framework community incorporated 13 C-enriched ('labelled') DOM, indicating widespread DOM uptake and recycling. Finally, the framework effectively retained 13 C-enriched phytodetritus, (a) by physical retention on the biofilm-covered surface and (b) by biological filtration through suspension-feeding fauna. We therefore suggest that the dead framework acts as a 'filtration-recycling factory' that enhances the metabolic activity of CWC reefs. The exposed framework, however, is particularly vulnerable to ocean acidification, jeopardizing this important aspect of CWC reef functioning. Graphical abstract: Image 1 Highlights: Video analysis shows that dead framework forms the largest habitat on a coral mound. Dead framework contributes substantially to reef biomass and metabolic activity. Dead framework retains phytodetritus on its surface and by active suspension feeders. The community takes up dissolved organic carbon at ambient reef concentration. Production of ammonium and nitrate indicate complex nitrogen cycling.